Liquid composite carbon source for sewage treatment and preparation method thereof
By adopting a liquid composite carbon source with specific composition and preparation process, the problem of insufficient denitrification performance of wastewater treatment in the prior art is solved, excellent denitrification effect and carbon release rate are achieved, and the quality of the product and market prospects are improved.
Patent Information
- Application Number
- CN202411090952.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-09
AI Technical Summary
The existing liquid composite carbon sources used for sewage treatment have shortcomings in nitrogen removal performance and need further improvement to improve their effects.
Use a liquid composite carbon source composed of plant liquid, functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nanopowder, and through specific preparation processes, including sonication, soaking and drying, etc. Steps to prepare a product with excellent nitrogen removal performance.
It realizes excellent denitrification performance and good carbon release rate performance of liquid composite carbon sources in wastewater treatment, effectively ensuring the quality and quality of the product.
Smart Images

Figure BDA0004986558800000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment agent production, in particular to a liquid composite carbon source for sewage treatment and a preparation method thereof. Background Art
[0002] The main reason for water pollution is that the nitrogen content in the water exceeds the standard. Urban domestic sewage, animal feces, farmland irrigation, and various polluted factory wastewater are the main factors for excessive nitrogen in the water. Excessive nitrogen content will cause serious harm to the ecosystem and human health, and will also cause eutrophication of water bodies. Due to the excessive supply of nitrogen in the water, seaweed will reproduce in large quantities, making the water system very chaotic, causing the oxygen concentration in the water to decrease, thus endangering aquatic life. In addition, excessive nitrogen concentration will cause certain harm to the human body, such as cancer, physical defects and fertility disorders.
[0003] In the patent document with application number "CN202311536444.2" and name "A liquid composite carbon source for sewage treatment", it is recorded that "the technical solution uses the soaking liquid of agricultural waste as a solvent, constructs a dispersed system with a low-concentration composite carbon source, and adds trace elements and components such as potassium and phosphorus to provide comprehensive and rich nutritional conditions for water treatment microorganisms. Specifically, this composite carbon source uses boric acid, manganese chloride, zinc sulfate, and copper sulfate as trace elements, and constructs a composition with sodium nitrate, potassium dihydrogen phosphate, ammonium ferric citrate, EDTA-disodium, sodium carbonate, calcium acetate, sodium acetate, glucose, and potassium lactate, and the composition is dissolved in the soaking liquid of corn straw and rice husk. The resulting composite carbon source achieves a good growth-promoting effect at a lower nutrient concentration. The present invention is not only easy to be absorbed and utilized by water treatment microorganisms, but also easy to prepare and low in cost. It also achieves a certain degree of waste utilization and has significant technical advantages."
[0004] Although the liquid composite carbon source produced by the above patent document has advantages such as waste utilization, its denitrification performance is relatively insufficient and still needs further improvement. Based on this, the present invention provides a liquid composite carbon source for sewage treatment and a preparation method thereof to solve the above technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide a liquid composite carbon source for sewage treatment and a preparation method thereof. The prepared liquid composite carbon source for sewage treatment not only has a good carbon release rate performance, but also has excellent denitrification performance, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The first aspect of the present invention provides a liquid composite carbon source for sewage treatment, which is composed of the following raw materials in parts by weight: 100 to 120 parts of plant liquid, 3 to 6 parts of functional fillers, 3 to 5 parts of functional additives, 2 to 4 parts of glucose, 4 to 7 parts of glycerol, 6 to 10 parts of sodium acetate, 4 to 7 parts of potassium lactate and 2 to 5 parts of compound nanopowder.
[0008] The present invention is further configured as follows: the preparation process of the plant liquid is as follows:
[0009] The composite base material is placed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL and ultrasonically fractionated for 20 to 30 minutes, then allowed to stand for 12 to 14 hours, filtered, and dried at a temperature of 40 to 50° C. to constant weight to obtain a first material;
[0010] The first material is placed in a calcium hydroxide solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a second material;
[0011] The second material is placed in a hydrochloric acid solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a third material;
[0012] The third material is placed in deionized water and ultrasonically treated for 8 to 10 hours at a solid-liquid ratio of 0.02 to 0.14 g / mL to obtain a plant solution.
[0013] The present invention is further configured as follows: the composite base material is formed by mixing pepper straw powder, reed straw powder and lettuce powder in a mass ratio of 0.12-0.32:0.25-0.45:1.
[0014] The present invention is further configured as follows: the preparation process of the functional filler is as follows:
[0015] Place appropriate amounts of polyvinyl alcohol and sodium alginate in a mixing device at a mass ratio of 1:0.04-0.08, and mix at 120-220 r / min for 60-80 min to obtain a mixture;
[0016] The mixture was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.005-0.08 g / mL for 30-40 min, and then placed in a water bath at 90-98° C. for ultrasonic treatment for 100-150 min. After cooling to room temperature, the composite carrier and sulfur were added thereto, and mixed at 80-100 r / min for 20-30 min to obtain a mixed solution;
[0017] The mixed solution is added dropwise into a 2% calcium chloride saturated boric acid mixed solution, and the obtained particles are washed 2 to 4 times with deionized water, dried, and then crushed into nano powder to obtain a functional filler.
[0018] The present invention is further configured as follows: the composite carrier is formed by mixing bentonite and limestone in a mass ratio of 1:0.2-0.4.
[0019] The present invention is further configured as follows: the addition amount of the composite carrier is 0.11-0.31% of the mass of the mixture, and the addition amount of the sulfur is 0.05-0.12% of the mass of the mixture.
[0020] The present invention is further configured as follows: the functional additive is any one of sodium sulfide, sodium thiosulfate and iron sulfide.
[0021] The present invention is further configured as follows: the compound nano powder is compounded by nano titanium dioxide and nano glass micro beads in a mass ratio of 1:0.5-0.8.
[0022] The second aspect of the present invention: also provides a method for preparing the above-mentioned liquid composite carbon source for sewage treatment, comprising the following steps:
[0023] Step 1: accurately weigh the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder, and put the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder into a mixing device for mixing and stirring to obtain a mixed material;
[0024] Step 2: placing the obtained mixed material in the plant liquid and mixing it at 120-140 r / min for 100-120 min;
[0025] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain a finished liquid composite carbon source for sewage treatment.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the present invention, plant liquid, functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder are used as raw materials, and the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder are put into a mixing device for mixing and stirring to obtain a mixed material, and then the obtained mixed material is placed in the plant liquid for mixing, and after the mixing is completed, it is discharged, and then it is successively inspected and metered and packaged to finally obtain a finished liquid composite carbon source for sewage treatment. The liquid composite carbon source for sewage treatment prepared by the present invention not only has a good carbon release rate performance, but also has excellent denitrification performance, which effectively guarantees its quality. The liquid composite carbon source for sewage treatment provided by the present invention and its preparation method have a broader market prospect and are more suitable for promotion. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The present embodiment provides a liquid composite carbon source for sewage treatment, which is composed of the following raw materials in parts by weight: 100 to 120 parts of plant liquid, 3 to 6 parts of functional fillers, 3 to 5 parts of functional additives, 2 to 4 parts of glucose, 4 to 7 parts of glycerol, 6 to 10 parts of sodium acetate, 4 to 7 parts of potassium lactate and 2 to 5 parts of compound nanopowder.
[0031] The preparation process of the plant liquid is as follows:
[0032] The composite base material is placed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL and ultrasonically fractionated for 20 to 30 minutes, then allowed to stand for 12 to 14 hours, filtered, and dried at a temperature of 40 to 50° C. to constant weight to obtain a first material;
[0033] The first material is placed in a calcium hydroxide solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a second material;
[0034] The second material is placed in a hydrochloric acid solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a third material;
[0035] The third material is placed in deionized water and ultrasonically treated for 8 to 10 hours at a solid-liquid ratio of 0.02 to 0.14 g / mL to obtain a plant solution.
[0036] Furthermore, the composite base material is mixed with pepper straw powder, reed straw powder and lettuce powder in a mass ratio of 0.12-0.32:0.25-0.45:1.
[0037] In this embodiment, it should be noted that:
[0038] In addition, the preparation process of the functional filler is as follows:
[0039] Place appropriate amounts of polyvinyl alcohol and sodium alginate in a mixing device at a mass ratio of 1:0.04-0.08, and mix at 120-220 r / min for 60-80 min to obtain a mixture;
[0040] The mixture was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.005-0.08 g / mL for 30-40 min, and then placed in a water bath at 90-98° C. for ultrasonic treatment for 100-150 min. After cooling to room temperature, the composite carrier and sulfur were added thereto, and mixed at 80-100 r / min for 20-30 min to obtain a mixed solution;
[0041] The mixed solution is added dropwise into a 2% calcium chloride saturated boric acid mixed solution, and the obtained particles are washed 2 to 4 times with deionized water, dried, and then crushed into nano powder to obtain a functional filler.
[0042] In this embodiment, it should be noted that polyvinyl alcohol was purchased from Sinopharm Chemical Reagent Co., Ltd., and sodium alginate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0043] The composite carrier is formed by mixing bentonite and limestone in a mass ratio of 1:0.2 to 0.4.
[0044] In this embodiment, it should be noted that bentonite was purchased from Shandong Yonglian New Material Technology Co., Ltd., and limestone was purchased from Hebei Leijiang New Material Technology Co., Ltd.
[0045] The added amount of the composite carrier is 0.11-0.31% of the mass of the mixture, and the added amount of the sulfur is 0.05-0.12% of the mass of the mixture.
[0046] The functional additive is any one of sodium sulfide, sodium thiosulfate and iron sulfide.
[0047] The compound nano powder is compounded by nano titanium dioxide and nano glass micro beads in a mass ratio of 1:0.5-0.8.
[0048] In this embodiment, it should be noted that the nano glass beads were purchased from Anhui Kaisheng Basic Materials Technology Co., Ltd.
[0049] In addition, this embodiment also provides a method for preparing the above-mentioned liquid composite carbon source for sewage treatment, comprising the following steps:
[0050] Step 1: accurately weigh the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder, and put the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder into a mixing device for mixing and stirring to obtain a mixed material;
[0051] Step 2: placing the obtained mixed material in the plant liquid and mixing it at 120-140 r / min for 100-120 min;
[0052] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain a finished liquid composite carbon source for sewage treatment.
[0053] Example 2
[0054] The preparation method of the liquid composite carbon source for sewage treatment provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the liquid composite carbon source for sewage treatment in this embodiment are different; the specific raw material composition and the specific preparation method of the liquid composite carbon source for sewage treatment in this embodiment are as follows:
[0055] A liquid composite carbon source for sewage treatment is composed of the following raw materials in parts by weight: 100-120 parts of plant liquid, 3-6 parts of functional fillers, 3-5 parts of functional additives, 2-4 parts of glucose, 4-7 parts of glycerol, 6-10 parts of sodium acetate, 4-7 parts of potassium lactate and 2-5 parts of composite nano powder.
[0056] The preparation process of the plant liquid is as follows:
[0057] The composite base material is placed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL and ultrasonically fractionated for 20 to 30 minutes, then allowed to stand for 12 to 14 hours, filtered, and dried at a temperature of 40 to 50° C. to constant weight to obtain a first material;
[0058] The first material is placed in a calcium hydroxide solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a second material;
[0059] The second material is placed in a hydrochloric acid solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a third material;
[0060] The third material is placed in deionized water and ultrasonically treated for 8 to 10 hours at a solid-liquid ratio of 0.02 to 0.14 g / mL to obtain a plant solution.
[0061] Furthermore, the composite base material is mixed with pepper straw powder, reed straw powder and lettuce powder in a mass ratio of 0.12-0.32:0.25-0.45:1.
[0062] In this embodiment, it should be noted that:
[0063] In addition, the preparation process of the functional filler is as follows:
[0064] Place appropriate amounts of polyvinyl alcohol and sodium alginate in a mixing device at a mass ratio of 1:0.04-0.08, and mix at 120-220 r / min for 60-80 min to obtain a mixture;
[0065] The mixture was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.005-0.08 g / mL for 30-40 min, and then placed in a water bath at 90-98° C. for ultrasonic treatment for 100-150 min. After cooling to room temperature, the composite carrier and sulfur were added thereto, and mixed at 80-100 r / min for 20-30 min to obtain a mixed solution;
[0066] The mixed solution is added dropwise into a 2% calcium chloride saturated boric acid mixed solution, and the obtained particles are washed 2 to 4 times with deionized water, dried, and then crushed into nano powder to obtain a functional filler.
[0067] In this embodiment, it should be noted that polyvinyl alcohol was purchased from Sinopharm Chemical Reagent Co., Ltd., and sodium alginate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0068] The composite carrier is formed by mixing bentonite and limestone in a mass ratio of 1:0.2 to 0.4.
[0069] In this embodiment, it should be noted that bentonite was purchased from Shandong Yonglian New Material Technology Co., Ltd., and limestone was purchased from Hebei Leijiang New Material Technology Co., Ltd.
[0070] The added amount of the composite carrier is 0.11-0.31% of the mass of the mixture, and the added amount of the sulfur is 0.05-0.12% of the mass of the mixture.
[0071] The functional additive is any one of sodium sulfide, sodium thiosulfate and iron sulfide.
[0072] The compound nano powder is compounded by nano titanium dioxide and nano glass micro beads in a mass ratio of 1:0.5-0.8.
[0073] In this embodiment, it should be noted that the nano glass beads were purchased from Anhui Kaisheng Basic Materials Technology Co., Ltd.
[0074] In addition, this embodiment also provides a method for preparing the above-mentioned liquid composite carbon source for sewage treatment, comprising the following steps:
[0075] Step 1: accurately weigh the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder, and put the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder into a mixing device for mixing and stirring to obtain a mixed material;
[0076] Step 2: placing the obtained mixed material in the plant liquid and mixing it at 120-140 r / min for 100-120 min;
[0077] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain a finished liquid composite carbon source for sewage treatment.
[0078] Example 3
[0079] The preparation method of the liquid composite carbon source for sewage treatment provided in this embodiment is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation method of the liquid composite carbon source for sewage treatment in this embodiment are different; the specific raw material composition and the specific preparation method of the liquid composite carbon source for sewage treatment in this embodiment are as follows:
[0080] A liquid composite carbon source for sewage treatment is composed of the following raw materials in parts by weight: 100-120 parts of plant liquid, 3-6 parts of functional fillers, 3-5 parts of functional additives, 2-4 parts of glucose, 4-7 parts of glycerol, 6-10 parts of sodium acetate, 4-7 parts of potassium lactate and 2-5 parts of composite nano powder.
[0081] The preparation process of the plant liquid is as follows:
[0082] The composite base material is placed in deionized water at a solid-liquid ratio of 0.05 to 0.12 g / mL and ultrasonically fractionated for 20 to 30 minutes, then allowed to stand for 12 to 14 hours, filtered, and dried at a temperature of 40 to 50° C. to constant weight to obtain a first material;
[0083] The first material is placed in a calcium hydroxide solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a second material;
[0084] The second material is placed in a hydrochloric acid solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a third material;
[0085] The third material is placed in deionized water and ultrasonically treated for 8 to 10 hours at a solid-liquid ratio of 0.02 to 0.14 g / mL to obtain a plant solution.
[0086] Furthermore, the composite base material is mixed with pepper straw powder, reed straw powder and lettuce powder in a mass ratio of 0.12-0.32:0.25-0.45:1.
[0087] In this embodiment, it should be noted that:
[0088] In addition, the preparation process of the functional filler is as follows:
[0089] Place appropriate amounts of polyvinyl alcohol and sodium alginate in a mixing device at a mass ratio of 1:0.04-0.08, and mix at 120-220 r / min for 60-80 min to obtain a mixture;
[0090] The mixture was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.005-0.08 g / mL for 30-40 min, and then placed in a water bath at 90-98° C. for ultrasonic treatment for 100-150 min. After cooling to room temperature, the composite carrier and sulfur were added thereto, and mixed at 80-100 r / min for 20-30 min to obtain a mixed solution;
[0091] The mixed solution is added dropwise into a 2% calcium chloride saturated boric acid mixed solution, and the obtained particles are washed 2 to 4 times with deionized water, dried, and then crushed into nano powder to obtain a functional filler.
[0092] In this embodiment, it should be noted that polyvinyl alcohol was purchased from Sinopharm Chemical Reagent Co., Ltd., and sodium alginate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0093] The composite carrier is formed by mixing bentonite and limestone in a mass ratio of 1:0.2 to 0.4.
[0094] In this embodiment, it should be noted that bentonite was purchased from Shandong Yonglian New Material Technology Co., Ltd., and limestone was purchased from Hebei Leijiang New Material Technology Co., Ltd.
[0095] The added amount of the composite carrier is 0.11-0.31% of the mass of the mixture, and the added amount of the sulfur is 0.05-0.12% of the mass of the mixture.
[0096] The functional additive is any one of sodium sulfide, sodium thiosulfate and iron sulfide.
[0097] The compound nano powder is compounded by nano titanium dioxide and nano glass micro beads in a mass ratio of 1:0.5-0.8.
[0098] In this embodiment, it should be noted that the nano glass beads were purchased from Anhui Kaisheng Basic Materials Technology Co., Ltd.
[0099] In addition, this embodiment also provides a method for preparing the above-mentioned liquid composite carbon source for sewage treatment, comprising the following steps:
[0100] Step 1: accurately weigh the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder, and put the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder into a mixing device for mixing and stirring to obtain a mixed material;
[0101] Step 2: placing the obtained mixed material in the plant liquid and mixing it at 120-140 r / min for 100-120 min;
[0102] Step 3: After the mixing is completed, the materials are discharged, and then inspected, measured and packaged in sequence to finally obtain a finished liquid composite carbon source for sewage treatment.
[0103] Comparative Example 1: The difference from Example 1 is that in this example, an equal amount of composite base material is placed in deionized water for ultrasonic treatment for 8 to 10 hours instead of plant liquid.
[0104] Comparative Example 2: The difference from Example 1 is that this example does not contain functional fillers.
[0105] Performance test: The liquid composite carbon source samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the liquid composite carbon sources provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows:
[0106] 1. Carbon release capacity test: The test method is to take 10g of each group of composite carbon sources, put them in 400mL of water, seal them and shake them at room temperature, take samples and filter them after 12h and 48h respectively, and use rapid digestion spectrophotometry to measure the carbon release amount (CODcr) in the samples.
[0107] 2. Static denitrification test: The test method is to boil tap water to remove chlorine, then add potassium nitrate and potassium dihydrogen phosphate to obtain artificial wastewater with N:P=5:1. Take 200mL of artificial wastewater from each group, the nitrate concentration is 25mg / L, add 0.2g of sweet denitrifying bacteria and 5g of composite carbon source to each group, seal and shake, and culture continuously. Determine NO3 before culture and after 3d and 18d. - -N concentration characterizes its denitrification performance.
[0108] The obtained test data are recorded in Table 1 and Table 2 below:
[0109] Table 1 Carbon release performance test results of each group of liquid composite carbon sources
[0110] Group 12h(CODcr(mg / g)) 48h(CODcr(mg / g)) Example 1 Group 11.56 30.12 Example 2 Group 11.73 30.46 Example 3 Group 11.48 29.98 Comparison group 1 14.55 33.11 Comparison of 2 groups 14.13 32.88
[0111] Table 2 Denitrification test results of each group of liquid composite carbon sources
[0112]
[0113] By comparing and analyzing the relevant data in Table 1 and Table 2, it can be seen that the liquid composite carbon source for sewage treatment prepared by the present invention not only has a good carbon release rate performance, but also has excellent denitrification performance, effectively ensuring its quality. This shows that the liquid composite carbon source for sewage treatment and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0114] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0115] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A liquid composite carbon source for sewage treatment, characterized in that: The invention is composed of the following raw materials in parts by weight: 100 to 120 parts of plant liquid, 3 to 6 parts of functional fillers, 3 to 5 parts of functional additives, 2 to 4 parts of glucose, 4 to 7 parts of glycerol, 6 to 10 parts of sodium acetate, 4 to 7 parts of potassium lactate and 2 to 5 parts of compound nano powder; The preparation process of the plant liquid is as follows: The composite base material is placed in deionized water for ultrasonic dispersion at a solid-liquid ratio of 0.05 to 0.12 g / mL for 20 to 30 minutes, then allowed to stand for 12 to 14 hours, filtered, and dried at 40 to 50° C. to constant weight to obtain a first material; The first material is placed in a calcium hydroxide solution with a concentration of 2-4% and soaked for 12-14 hours at a solid-liquid ratio of 0.02-0.12 g / mL, filtered, washed with deionized water 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a second material; The second material is placed in a hydrochloric acid solution with a concentration of 2-4% at a solid-liquid ratio of 0.02-0.12 g / mL and soaked for 12-14 hours, filtered and washed with deionized water for 2-4 times, and then placed in an oven at 50° C. and dried to constant weight to obtain a third material; placing the third material in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.02 to 0.14 g / mL for 8 to 10 hours to obtain a plant solution; The composite base material is prepared by mixing pepper straw powder, reed straw powder and lettuce powder in a mass ratio of 0.12-0.32:0.25-0.45:1; The preparation process of the functional filler is as follows: Put polyvinyl alcohol and sodium alginate in a mixing device at a mass ratio of 1:0.04-0.08, and mix them at 120-220 r / min for 60-80 min to obtain a mixture; The mixture was placed in deionized water for ultrasonic treatment at a solid-liquid ratio of 0.005-0.08 g / mL for 30-40 min, and then placed in a water bath at 90-98° C. for ultrasonic treatment for 100-150 min. After cooling to room temperature, the composite carrier and sulfur were added thereto, and mixed at 80-100 r / min for 20-30 min to obtain a mixed solution; The mixed solution is added dropwise to a 2% calcium chloride saturated boric acid mixed solution, and the obtained particles are washed 2 to 4 times with deionized water, dried, and crushed into nano powder to obtain a functional filler; The composite carrier is made of bentonite and limestone mixed in a mass ratio of 1:0.2-0.4; The functional additive is any one of sodium sulfide, sodium thiosulfate, and iron sulfide; The compound nano powder is compounded by nano titanium dioxide and nano glass micro beads in a mass ratio of 1:0.5-0.
8.
2. A liquid composite carbon source for sewage treatment according to claim 1, characterized in that: The added amount of the composite carrier is 0.11-0.31% of the mass of the mixture, and the added amount of the sulfur is 0.05-0.12% of the mass of the mixture.
3. A method for preparing a liquid composite carbon source for sewage treatment according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: accurately weigh the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder, and put the functional filler, functional additive, glucose, glycerol, sodium acetate, potassium lactate and compound nano powder into a mixing device for mixing and stirring to obtain a mixed material; Step 2: placing the obtained mixed material in the plant liquid and mixing it at 120-140 r / min for 100-120 min; Step 3: After the mixing is completed, the material is discharged, and then inspected, measured and packaged in sequence to finally obtain a finished liquid composite carbon source for sewage treatment.
Citation Information
Patent Citations
Nitrogen and phosphorus removal filler for urban and municipal sewage and preparation method of nitrogen and phosphorus removal filler
CN113860497A
Solid-phase slow-release sulfur filler based on sulfur autotrophic nitrogen removal as well as preparation method and application of solid-phase slow-release sulfur filler
CN116605986A
Liquid composite carbon source as well as preparation method and application thereof
CN117185478A
Liquid composite carbon source for sewage treatment
CN117247147A
Citric acid composition biomass carbon source and preparation method thereof
CN117326702A